Characteristics and Outcomes of COVID-19 in Reproductive-Aged Pregnant and Nonpregnant Women in Osaka, Japan. (April 2022) - Zha, Ling; Sobue, Tomotaka; Hirayama, Atsushi; Takeuchi, Taro; Tanaka, Kenta; Katayama, Yusuke; Komukai, Sho; Shimazu, Takeshi; Kitamura, Tetsuhisa; ,
Highlights: There were 4, 156 COVID-19 notifications in females aged 10–49 years. Of the 4, 156 notifications, 29 (0.7%) were pregnant women. All pregnant women had mild or asymptomatic disease. Among women with COVID-19, pregnant women were more likely to be hospitalized. There were no intensive care unit admissions and no deaths due to COVID-19 in pregnant women. Abstract: Objective: To describe the clinical characteristics and outcomes of reproductive-aged female patients with coronavirus disease 2019 (COVID-19). Methods: We conducted a retrospective study of female patients aged 10–49 years, diagnosed with COVID-19 in Osaka, Japan, between January and November 2020. We assessed their epidemiological and clinical characteristics according to their pregnancy status. Results: A total of 4, 156 patients were enrolled, of whom 29 (0.7%) were pregnant. Most patients exhibited mild symptoms, and 10.8% of the cases were asymptomatic. No moderate or severe cases were observed in pregnant women, whereas only 0.1% of the nonpregnant women had severe disease at diagnosis. No clusters were observed in the pregnant patients; however, most acquired the infection from a family member. Of the 29 pregnant women, 22 (75.9%) were hospitalized; whereas among the nonpregnant women, 579 (14.0%) were hospitalized ( p < 0.001). No patients were admitted to the intensive care unit, and there were no deaths among women aged 10–49 years. Conclusions: Pregnant women accounted for 0.7% of the total cases of COVID-19 among women aged 10–49 years. Pregnant women were more likely to be hospitalized but generally had mild disease.